A dynamic general equilibrium model with technological innovations in the banking sector - Leão, E. R. (Journal of Economics (Zeitschrift für Nationalökonomie), 2003)
We use a dynamic general equilibrium model where banks are treated as profit maximizing firms. We examine the behavior of the model when there are technological innovations that are specific to the banking industry as well as technological innovations in nonbank firms. In a stochastic simulation experiment where the technological shocks in banks and the technological shocks in nonbank firms are identical and perfectly correlated, we are able to approximately replicate the contemporaneous correlation between banks' investment and real output and the contemporaneous correlation between work hours in banks and real output that we see in the data. With one exception, the correlations between banks' investment and the past and future values of real output that we obtained with our model have the same sign as in the data. With two exceptions, the correlations between work hours in banks and the past and future values of real output that we obtained have the same sign as in the data.